Study on division of groundwater function zones in Pingtan Island. Issue 2 (September 2019) - Huo, Yun; Li, Yuxi; Li, Wanglin; Zhang, Chunhui; PanlinLi
Abstract: Based on the topography, geomorphology, groundwater exploitation and other hydrogeological data of Pintan Island, the study area was divided into three levels and basic evaluation units were divided. According to the zoning principle of Technical Outline of Groundwater Function Zoning in China, and through the spatial analysis function of ArcGIS, the zoning index data was spatialized and the overlay analysis was carried out. The study area was divided into three types of first-level function zones and eight types of second-level function zones. Moreover, the groundwater function zones map of the study area was drawn. Relevant results can provide reference and basis for relevant departments to develop, utilize and protect groundwater.